Biocompatibility and osseointegration of nanostructured titanium dental implants in minipigs. Issue 6 (28th February 2020) - Hoornaert, Alain; Vidal, Luciano; Besnier, Romain; Morlock, Jean‐Francois; Louarn, Guy; Layrolle, Pierre
Abstract: Objectives: It is well known that surface treatments of dental implants have a great impact on their rate of osseointegration. The aim of this study was to compare the biocompatibility and the bone–implant contact (BIC) of titanium dental implants with different surface treatments. Material and methods: Test implants (Biotech Dental) had a nanostructured surface and control implants (Anthogyr) were grit‐blasted with biphasic calcium phosphate and acid‐etched surface. Both titanium implants were inserted in mandible and maxillary bones of 6 Yucatan minipigs for 4 and 12 weeks ( n  = 10 implants/group). Biocompatibility and osseointegration were evaluated by non‐decalcified histology and back‐scattered electron microscopy images. Results: The reading of histology sections by an antomo‐pathologist indicated that the test implants were considered non‐irritating to the surrounding tissues and thus biocompatible compared with control implants. The BIC values were higher for test than for control dental implants at both 4 and 12 weeks. Conclusions: In summary, the new nanostructured titanium dental implant is considered biocompatible and showed a better osseointegration than the control implant at both 4 and 12 weeks.